The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5301/jn.5000259
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ exchange inhibitor, KB-R7943, attenuates contrast-induced acute 
kidney injury

Abstract: Activation of the reverse mode of NCX, followed by ET-1 overproduction and increased oxidative stress, seems to play an important role in the pathogenesis of CI-AKI. The inhibitor of the reverse mode of NCX, KB-R7943, has renoprotective effects on CI-AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…It has been proven that the ER stress-induced apoptosis can be mediated by ROS [22] and that oxidative stress plays an important role in the pathogenesis of CI-AKI [12,23]. In the present study, the role of ROS in the ER stress-induced apoptosis in iopromide-treated NRK-52E cells was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the ER stress-induced apoptosis can be mediated by ROS [22] and that oxidative stress plays an important role in the pathogenesis of CI-AKI [12,23]. In the present study, the role of ROS in the ER stress-induced apoptosis in iopromide-treated NRK-52E cells was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + /Ca 2+ exchanger system is one of the main pathways of intracellular Ca 2+ overload. It has been demonstrated that in rats the pretreatment with KB-R7943, an inhibitor of the Na + /Ca 2+ exchanger system, significantly and dose-dependently suppressed the increase of serum creatinine following diatrizoate administration [210]. The increase in intracellular calcium provokes a vasoconstrictive response in intrarenal circulation and would be an important mediator of epithelial cell apoptosis and necrosis.…”
Section: Contrast-induced Nephropathymentioning
confidence: 99%
“…The rationale is based on the fact that while in normal subjects, the Na + –Ca 2+ exchanger pumps Ca 2+ outside the renal tubular epithelial cells to keep intracellular Ca 2+ low, under the effect of contrast drugs the Na + –Ca 2+ exchanger can reversibly extrude Na + for Ca 2+ influx, thereby leading to intracellular Ca 2+ overload, which is considered a key factor in ischemic cell injury and in CI-AKI 135137. (Figure 1).…”
Section: Prevention Of Ci-akimentioning
confidence: 99%